Gel-coating modified aqueous zinc-ion battery anode material and preparation method thereof
Patent Information
- Application Number
- CN202610870972.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-06-08
- Filing Date
- 2026-06-16
- Publication Date
- 2026-10-30
AI Technical Summary
但是目前水系锌离子电池负极的界面修饰主要依靠传统人工界面层,而传统人工界面层难以在长循环中维持结构完整性,常在体积变化下开裂失效;同时,传统人工界面层的致密涂层与高效离子传导之间存在固有矛盾,难以协同实现耐腐蚀与高倍率性能
本申请的水系锌离子电池负极材料具有较小的电荷转移和离子扩散电阻,展示出优良的电化学性能。本申请的水系锌离子电池负极材料经凝胶涂层改性而具有致密阻隔特性,既能有效抑制锌枝晶不可控生长与水相关副反应,又能借助聚合物链上富含的羧基(COO-)与磺酸基(
SO3-)官能团,通过特定加料顺序与静置陈化工艺实现的均匀分布,引导锌离子均匀成核与沉积,同时通过该有机凝胶涂层的柔性聚合物网络产生弹性缓冲,自适应锌沉积/溶解过程中的体积变化,避免涂层开裂失效,提高电极的结构完整性,综合提升电池的循环寿命与库仑效率,显著提升锌负极在电解液中的沉积溶解稳定性。
Smart Images

Figure CN123017912A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aqueous zinc-ion battery technology, and more specifically, to a gel-coated modified aqueous zinc-ion battery anode material and its preparation method. Background Technology
[0002] Aqueous zinc-ion batteries are among the most promising electrochemical energy storage devices, boasting advantages such as high theoretical mass capacity, ultra-high volumetric capacity, low redox potential, abundant natural reserves, and low cost of zinc anodes. However, the hydrogen evolution reaction induced by aqueous electrolytes leads to parasitic side reactions, reduced coulombic efficiency, and rapid capacity decay. Inhomogeneous Zn deposition / stripping during the zinc deposition / stripping process further exacerbates these issues. 2+ Flux can induce localized current hotspots, accelerating dendrite nucleation and tip-driven growth, which may puncture the separator and ultimately lead to internal short-circuit failure. These factors hinder the practical application of aqueous zinc-ion batteries.
[0003] Zinc anode interface modification and gel electrolyte optimization strategies can effectively suppress side reactions and improve zinc metal utilization, thereby improving battery performance. However, current interface modification of aqueous zinc-ion battery anodes mainly relies on traditional artificial interface layers. These layers often fail due to cracking under volume changes, as they struggle to maintain structural integrity during long-term cycling. Furthermore, there is an inherent contradiction between the dense coating and efficient ion conduction of traditional artificial interface layers, making it difficult to achieve both corrosion resistance and high-rate performance. Moreover, the difficulty in precisely controlling the fabrication process often leads to uneven distribution of functional groups within the coating, inducing localized electric field inhomogeneity and exacerbating dendrite growth. Summary of the Invention
[0004] To address the aforementioned problems in the existing technology, the present invention aims to provide a gel-coated modified aqueous zinc-ion battery anode material and its preparation method.
[0005] To solve the above problems, the technical solution adopted by the present invention is as follows: In a first aspect, this application provides a gel-coated modified aqueous zinc-ion battery anode material, comprising: Zinc matrix; and, A gel coating formed on the zinc substrate.
[0006] In some embodiments, the gel coating is formed by uniformly dispersing a polysaccharide anionic polyelectrolyte in a solution of a functional material and then sequentially allowing it to stand at room temperature for aging and undergoing ultrasonic degassing. The functional material contains sulfonic acid groups, and the polysaccharide anionic polyelectrolyte contains free carboxyl groups.
[0007] In some embodiments, the polysaccharide anionic polyelectrochemical material includes sodium alginate (SA), sodium carboxymethyl cellulose (CMC); and / or, The functional materials include sodium lignosulfonate (SLS) and sulfobetaine methacrylate (SBMA).
[0008] Secondly, this application provides a method for preparing a gel-coated modified aqueous zinc-ion battery anode material, the preparation method comprising: Step S100: Add functional materials to deionized water to form a solution, and uniformly disperse polysaccharide anionic polyelectric materials in the solution. After stirring, allow the mixture to stand at room temperature for aging and then degas it by ultrasonication to form a gel coating precursor. The functional materials contain sulfonic acid groups, and the polysaccharide anionic polyelectric materials contain free carboxyl groups. Step S200: Coat the gel coating precursor onto the surface of the pretreated zinc substrate and dry it in a vacuum environment to obtain the gel coating modified aqueous zinc-ion battery anode material.
[0009] In some embodiments, the polysaccharide anionic polyelectrochemical material includes sodium alginate (SA), sodium carboxymethyl cellulose (CMC); and / or, The functional materials include sodium lignosulfonate (SLS) and sulfobetaine methacrylate (SBMA).
[0010] In some embodiments, the time for aging at room temperature is 2-10 hours, and the temperature is 20-30°C.
[0011] In some embodiments, the amount of polysaccharide anionic polyelectrolyte rich in free carboxyl groups is 0.2-1 g, the amount of functional component rich in sulfonic acid groups is 0.01-0.1 g, and the amount of deionized water is 10-20 mL.
[0012] In some embodiments, the thickness of the gel coating precursor coated on the zinc substrate surface is 100~250 μm.
[0013] In a third aspect, this application provides an aqueous zinc-ion battery, comprising an electrode sheet prepared from an aqueous zinc-ion battery negative electrode material prepared according to the aqueous zinc-ion battery negative electrode material as described above or prepared by the method described above.
[0014] In some embodiments, the aqueous zinc-ion battery includes coin cells and full cells.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: The aqueous zinc-ion battery anode material of this application exhibits low charge transfer and ion diffusion resistance, demonstrating excellent electrochemical performance. This aqueous zinc-ion battery anode material, modified with a gel coating, possesses dense barrier properties, effectively suppressing uncontrolled zinc dendrite growth and water-related side reactions, while also utilizing the abundant carboxyl groups on the polymer chain (…). COO - ) and sulfonic acid group ( SO3 - The functional groups, through a specific feeding sequence and static aging process, achieve uniform distribution, guiding the uniform nucleation and deposition of zinc ions. At the same time, the flexible polymer network of the organic gel coating generates an elastic buffer, adapting to the volume changes during the zinc deposition / dissolution process, avoiding coating cracking and failure, improving the structural integrity of the electrode, comprehensively improving the cycle life and coulombic efficiency of the battery, and significantly improving the deposition and dissolution stability of the zinc anode in the electrolyte.
[0016] Functional components rich in sulfonic acid groups effectively prevent localized aggregation of subsequently added polysaccharide macromolecules (SA / CMC). Meanwhile, anionic polysaccharide materials rich in free carboxyl groups, due to the abundance of carboxyl groups on their molecular chains... COO - This material possesses excellent hydrophilicity, biocompatibility, and the ability to form thermally irreversible gels through ionic bonds (such as with divalent zinc ions). The polysaccharide-based anionic polymer is dissolved in a solution of functional materials (formed by dissolving the functional materials in deionized water), allowing the sulfonic acid-rich functional components to achieve uniform molecular-level dispersion within the polysaccharide matrix. The functional components and the polysaccharide-based anionic polymer are fully interwoven and entangled, resulting in excellent cycle stability for the modified anode material. While ensuring the material's mechanical stability and ion transport performance, it effectively regulates zinc ion migration behavior and interfacial interactions, improving the cycle stability and safety performance of aqueous zinc-ion batteries. Compared with the shortcomings of existing inorganic rigid coatings, such as easy cracking and failure, and the lack of active ion flux control capability and complex preparation process of ordinary polymer coatings, the core advantage of this invention lies in the specific feeding sequence of first introducing components rich in sulfonic acid groups and then dissolving polysaccharide macromolecules and the static aging process. This achieves uniform dispersion of two active functional groups in the coating in a simple scraping method, avoiding the local aggregation problem in conventional methods. At the same time, the gel coating can evolve into a porous gel network structure in situ during cycling, which can dynamically and elastically buffer and adapt to volume changes, taking into account both excellent corrosion resistance and fast ion transport capability, and ultimately improving the stable cycle life of the modified zinc anode to more than 2000 hours. Attached Figure Description
[0017] Figure 1 The images show scanning electron microscope (SEM) images of the surface morphology of the aqueous zinc-ion battery anode materials prepared in Examples 1 to 4. Figure 1 In the text, a, b, c, and d correspond to Example 1, Example 2, Example 3, and Example 4, respectively. Figure 2 The images show scanning electron microscope (SEM) images of the surface morphology of the aqueous zinc-ion battery anode materials prepared in Comparative Examples 1 to 6. Figure 2In the middle, a to f correspond to proportions 1 to 6 respectively; Figure 3 Comparison of electrochemical impedance spectroscopy (EIS) of the corresponding symmetrical cells of the aqueous zinc-ion battery anode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 6; Figure 4 The aqueous zinc-ion battery anode materials prepared in Examples 1 and 3 and Comparative Examples 1, 2, and 5 correspond to symmetrical cells at 0.5 mA cm⁻¹. -2 Comparison of cycling performance at current density; Figure 5 The aqueous zinc-ion battery anode materials prepared in Examples 2 and 4 and Comparative Examples 3, 4, and 6 correspond to symmetrical cells at 0.5 mA cm⁻¹. -2 Comparison of cycling performance at current density; Figure 6 The aqueous zinc-ion battery anode material prepared for Comparative Example 7 corresponds to a symmetrical cell at 0.5 mA cm⁻¹. -2 Comparison of cycling performance at current density. Detailed Implementation
[0018] This invention provides a gel-coated modified aqueous zinc-ion battery anode material and its preparation method. It achieves molecular-level uniform dispersion through a specific feeding sequence of functional materials and polysaccharide anionic polymeric materials and a static aging process, thereby constructing a stable gel coating in situ. The modified aqueous zinc-ion battery anode material has low charge transfer and ion diffusion resistance.
[0019] This application provides a method for preparing a gel-coated modified aqueous zinc-ion battery anode material, comprising the following steps S100 to S200: Step S100: adding functional materials to deionized water to form a solution, and uniformly dispersing polysaccharide anionic polymeric materials in the solution, stirring, and then sequentially allowing it to stand at room temperature for aging and ultrasonic degassing to form a gel coating precursor; Step S200: coating the gel coating precursor onto the surface of a pretreated zinc substrate and drying it in a vacuum environment to obtain the gel-coated modified aqueous zinc-ion battery anode material.
[0020] This application provides a gel-coated modified aqueous zinc-ion battery anode material, comprising: a zinc substrate; and a gel coating formed on the zinc substrate. The gel coating is formed by uniformly dispersing a polysaccharide anionic polymeric material in a solution of a functional material, followed by sequential aging at room temperature and ultrasonic degassing. The functional material contains sulfonic acid groups, and the polysaccharide anionic polymeric material contains free carboxyl groups. Exemplarily, the polysaccharide anionic polymeric material includes sodium alginate (SA) and sodium carboxymethyl cellulose (CMC). Exemplarily, the functional material includes sodium lignosulfonate (SLS) and sulfobetaine methacrylate (SBMA). For example, the amount of polysaccharide anionic polyelectrolyte rich in free carboxyl groups is 0.2~1g, such as 0.2g, 0.3g, 0.5g, 0.8g, or 1g; the amount of functional component rich in sulfonic acid groups is 0.01~0.1g, such as 0.01g, 0.02g, 0.05g, 0.08g, or 0.1g; and the amount of deionized water is 10~20mL, such as 10mL, 12mL, 15mL, 18mL, 19mL, or 20mL. For example, the thickness of the gel coating precursor coated on the zinc substrate surface is 100~250μm, such as 100μm, 120μm, 145μm, 176μm, 180μm, 202μm, 230μm, or 250μm. For example, the time for standing and aging at room temperature is 2h, 3h, 3.5h, 6h, 7.8h, 8.3h, 9h, and 10h, and the temperature is 20℃, 22℃, 23℃, 27℃, 28.2℃, 29℃, and 30℃.
[0021] The present invention will be further described below with reference to specific embodiments and comparative examples.
[0022] Example 1 (Notation: SLS+SA) Preparation of gel-coated modified aqueous zinc-ion battery anode material.
[0023] The preparation method includes the following steps S100 to S200: Step S100: First, add 0.02g of sodium lignosulfonate (SLS) to 15mL of deionized water to form a solution. Then, dissolve 0.5g of sodium alginate (SA) in the above solution. Stir at 50℃ and 500rpm for 4h, then cool the solution to room temperature and let it stand for 6h. Finally, perform ultrasonic degassing for 30min to form the gel coating precursor.
[0024] Step S200: The gel coating precursor is coated onto the pretreated zinc substrate surface and dried in a vacuum environment to obtain the aqueous zinc-ion battery anode modification material. The zinc foil is first soaked in anhydrous ethanol and ultrasonically treated for 30 minutes to remove surface impurities, then placed in a vacuum drying oven for 30 minutes and dried. The gel coating precursor is then uniformly coated onto the zinc foil, and the foil is dried in a vacuum drying oven at 60°C for 10 minutes to obtain the gel-coated aqueous zinc-ion battery anode material, labeled as SLS+SA anode modification material.
[0025] Assembly of aqueous zinc-ion batteries.
[0026] The aqueous zinc-ion battery anode material prepared by the above method was used as the positive and negative electrode materials, the separator was a glass fiber separator, and the electrolyte was 2.0 M ZnSO4. A symmetrical battery was assembled.
[0027] Example 2 (Referred to as: SLS+ CMC) Preparation of gel-coated modified aqueous zinc-ion battery anode material.
[0028] The preparation method includes the following steps S100 to S200: Step S100: First, add 0.02g of sodium lignosulfonate (SLS) to 15mL of deionized water to form a solution. Then, dissolve 0.5g of sodium carboxymethyl cellulose (CMC) in the above solution. Stir at 50℃ and 500rpm for 4h, then cool the solution to room temperature and let it stand for 6h. Finally, perform ultrasonic degassing for 30min to form the gel coating precursor.
[0029] Step S200: First, immerse the zinc foil in anhydrous ethanol and sonicate it for 30 minutes to clean surface impurities. Then, place it in a vacuum drying oven for 30 minutes and remove it. Next, uniformly coat the gel coating precursor onto the zinc foil and place it in a vacuum drying oven at 60°C for 10 minutes to dry it. This yields the gel-coated modified aqueous zinc-ion battery anode material, labeled as SLS+CMC anode modified material.
[0030] Assembly of aqueous zinc-ion batteries.
[0031] The aqueous zinc-ion battery anode material prepared by the above method was used as the positive and negative electrode materials, the separator was a glass fiber separator, and the electrolyte was 2.0 M ZnSO4. A symmetrical battery was assembled.
[0032] Example 3 (Notation: SBMA + SA) Preparation of gel-coated modified aqueous zinc-ion battery anode material.
[0033] The preparation method includes the following steps S100 to S200: Step S100: First, add 0.02g of sulfobetaine methacrylate (SBMA) to 15mL of deionized water to form a solution. Then, dissolve 0.5g of sodium alginate (SA) in the above solution. Stir at 50℃ and 500rpm for 4h, then cool the solution to room temperature and let it stand for 6h. Finally, perform ultrasonic degassing for 30min to form the gel coating precursor.
[0034] Step S200: First, immerse the zinc foil in anhydrous ethanol and sonicate it for 30 minutes to clean surface impurities. Then, place it in a vacuum drying oven for 30 minutes and remove it. Next, uniformly coat the zinc foil with the gel coating precursor and dry it in a vacuum drying oven at 60°C for 10 minutes. This yields the gel-coated modified aqueous zinc-ion battery anode material, labeled as SBMA+SA anode modified material.
[0035] Assembly of aqueous zinc-ion batteries.
[0036] The aqueous zinc-ion battery anode material prepared by the above method was used as the positive and negative electrode materials, the separator was a glass fiber separator, and the electrolyte was 2.0 M ZnSO4. A symmetrical battery was assembled.
[0037] Example 4 (Note: SBMA + CMC) Preparation of gel-coated modified aqueous zinc-ion battery anode material.
[0038] The preparation method includes the following steps S100 to S200: Step S100: First, add 0.02g of sulfobetaine methacrylate (SBMA) to 15mL of deionized water to form a solution. Then, dissolve 0.5g of sodium carboxymethyl cellulose (CMC) in the above solution. Stir at 50℃ and 500rpm for 4h, then cool the solution to room temperature and let it stand for 6h. Finally, perform ultrasonic degassing for 30min to form the gel coating precursor.
[0039] Step S200: First, immerse the zinc foil in anhydrous ethanol and sonicate it for 30 minutes to clean surface impurities. Then, place it in a vacuum drying oven for 30 minutes and remove it. Next, uniformly coat the zinc foil with the gel coating precursor and dry it in a vacuum drying oven at 60°C for 10 minutes. This yields the gel-coated modified aqueous zinc-ion battery anode material, labeled as SBMA+CMC anode modified material.
[0040] Assembly of aqueous zinc-ion batteries.
[0041] The aqueous zinc-ion battery anode material prepared by the above method was used as the positive and negative electrode materials, the separator was a glass fiber separator, and the electrolyte was 2.0 M ZnSO4. A symmetrical battery was assembled.
[0042] Comparative Example 1 (Notation: SA+SLS) The preparation method includes the following steps S100 to S200: Step S100: First, add 0.5g of sodium alginate (SA) to 15mL of deionized water and stir at 50℃ until completely dissolved to form a high-viscosity solution. Then, dissolve 0.02g of sodium lignosulfonate (SLS) in the above high-viscosity solution and stir at 50℃ and 500rpm for 4h. After that, cool the solution to room temperature and let it stand for 6h, followed by ultrasonic degassing for 30min to form the comparative precursor.
[0043] Step S200: First, immerse the zinc foil in anhydrous ethanol and ultrasonically treat it for 30 minutes to clean surface impurities. Then, place it in a vacuum drying oven for 30 minutes and remove it. Next, uniformly coat the comparative precursor onto the zinc foil and place it in a vacuum drying oven at 60°C for 10 minutes. This yields the comparative precursor-modified aqueous zinc-ion battery anode material, labeled as SA+SLS anode modified material.
[0044] Assembly of aqueous zinc-ion batteries.
[0045] The aqueous zinc-ion battery anode material prepared by the above method was used as the positive and negative electrode materials, the separator was a glass fiber separator, and the electrolyte was 2.0 M ZnSO4. A symmetrical battery was assembled.
[0046] Comparative Example 2 (Noted as: SA+SBMA) The preparation method includes the following steps S100 to S200: Step S100: First, add 0.5g of sodium alginate (SA) to 15mL of deionized water and stir at 50℃ until completely dissolved to form a high-viscosity solution. Then, dissolve 0.02g of sulfobetaine methacrylate (SBMA) in the above high-viscosity solution and stir at 50℃ and 500rpm for 4h. After stirring, cool the solution to room temperature and let it stand for 6h, followed by ultrasonic degassing for 30min to form the comparative precursor.
[0047] Step S200: First, immerse the zinc foil in anhydrous ethanol and ultrasonically treat it for 30 minutes to clean surface impurities. Then, place it in a vacuum drying oven for 30 minutes and remove it. Next, uniformly coat the comparative precursor onto the zinc foil and place it in a vacuum drying oven at 60°C for 10 minutes. This yields the comparative precursor-modified aqueous zinc-ion battery anode material, labeled as SA+SBMA anode modified material.
[0048] Assembly of aqueous zinc-ion batteries.
[0049] The aqueous zinc-ion battery anode material prepared by the above method was used as the positive and negative electrode materials, the separator was a glass fiber separator, and the electrolyte was 2.0 M ZnSO4. A symmetrical battery was assembled.
[0050] Comparative Example 3 (Referred to as: CMC+SLS) The preparation method includes the following steps S100 to S200: Step S100: First, add 0.5g of sodium carboxymethyl cellulose (CMC) to 15mL of deionized water and stir at 50°C until completely dissolved to form a high-viscosity solution. Then, dissolve 0.02g of sodium lignosulfonate (SLS) in the above high-viscosity solution and stir at 50°C and 500rpm for 4 hours. After that, cool the solution to room temperature and let it stand for 6 hours, followed by ultrasonic degassing for 30 minutes to form the comparative precursor.
[0051] Step S200: First, immerse the zinc foil in anhydrous ethanol and ultrasonically treat it for 30 minutes to clean surface impurities. Then, place it in a vacuum drying oven for 30 minutes and remove it. Next, uniformly coat the comparative precursor onto the zinc foil and place it in a vacuum drying oven at 60°C for 10 minutes. This yields the aqueous zinc-ion battery anode material modified with the comparative precursor, labeled as CMC+SLS anode modified material.
[0052] Assembly of aqueous zinc-ion batteries.
[0053] The aqueous zinc-ion battery anode material prepared by the above method was used as the positive and negative electrode materials, the separator was a glass fiber separator, and the electrolyte was 2.0 M ZnSO4. A symmetrical battery was assembled.
[0054] Comparative Example 4 (Notated as: CMC+SBMA) The preparation method includes the following steps S100 to S200: Step S100: First, add 0.5g of sodium carboxymethyl cellulose (CMC) to 15mL of deionized water and stir at 50°C until completely dissolved to form a high-viscosity solution. Then, dissolve 0.02g of sulfobetaine methacrylate (SBMA) in the above high-viscosity solution and stir at 50°C and 500rpm for 4 hours. After that, cool the solution to room temperature and let it stand for 6 hours, followed by ultrasonic degassing for 30 minutes to form the comparative precursor.
[0055] Step S200: First, immerse the zinc foil in anhydrous ethanol and ultrasonically treat it for 30 minutes to clean surface impurities. Then, place it in a vacuum drying oven for 30 minutes and remove it. Next, uniformly coat the comparative precursor onto the zinc foil, and then place it in a vacuum drying oven at 60°C for 10 minutes and remove it. This yields the aqueous zinc-ion battery anode material modified with the comparative precursor, labeled as CMC+SBMA anode modified material.
[0056] Assembly of aqueous zinc-ion batteries.
[0057] The aqueous zinc-ion battery anode material prepared by the above method was used as the positive and negative electrode materials, the separator was a glass fiber separator, and the electrolyte was 2.0 M ZnSO4. A symmetrical battery was assembled.
[0058] Comparative Example 5 (Note: SA only) The preparation method includes the following steps S100 to S200: Step S100: Add 0.5g of sodium alginate (SA) to 15mL of deionized water and stir at 50°C until completely dissolved to form a high-viscosity solution. After stirring at 50°C and 500rpm for 4h, cool the solution to room temperature and let it stand for 6h. Then, perform ultrasonic degassing for 30min to form the comparative precursor.
[0059] Step S200: First, immerse the zinc foil in anhydrous ethanol and ultrasonically treat it for 30 minutes to clean surface impurities. Then, place it in a vacuum drying oven for 30 minutes and remove it. Next, uniformly coat the comparative precursor onto the zinc foil and place it in a vacuum drying oven at 60°C for 10 minutes. This yields the comparative precursor-modified aqueous zinc-ion battery anode material, labeled as SA anode modified material.
[0060] Assembly of aqueous zinc-ion batteries.
[0061] The aqueous zinc-ion battery anode material prepared by the above method was used as the positive and negative electrode materials, the separator was a glass fiber separator, and the electrolyte was 2.0 M ZnSO4. A symmetrical battery was assembled.
[0062] Comparative Example 6 (Note: CMC only) The preparation method includes the following steps S100 to S200: Step S100: Add 0.5g of sodium carboxymethyl cellulose (CMC) to 15mL of deionized water and stir at 50°C until completely dissolved to form a high-viscosity solution. After stirring at 50°C and 500rpm for 4h, cool the solution to room temperature and let it stand for 6h. Then, perform ultrasonic degassing for 30min to form the comparative precursor.
[0063] Step S200: First, immerse the zinc foil in anhydrous ethanol and ultrasonically treat it for 30 minutes to clean surface impurities. Then, place it in a vacuum drying oven for 30 minutes and remove it. Next, uniformly coat the comparative precursor onto the zinc foil and place it in a vacuum drying oven at 60°C for 10 minutes. This yields the comparative precursor-modified aqueous zinc-ion battery anode material, labeled as CMC anode modified material.
[0064] Assembly of aqueous zinc-ion batteries.
[0065] The aqueous zinc-ion battery anode material prepared by the above method was used as the positive and negative electrode materials, the separator was a glass fiber separator, and the electrolyte was 2.0 M ZnSO4. A symmetrical battery was assembled.
[0066] Comparative Example 7 (Recorded as: SLS+ SA (unaged)) Preparation of gel-coated modified aqueous zinc-ion battery anode material.
[0067] The preparation method includes the following steps S100 to S200: Step S100: First, add 0.02g of sodium lignosulfonate (SLS) to 15mL of deionized water to form a solution. Then, dissolve 0.5g of sodium alginate (SA) in the above solution. After stirring at 50℃ and 500rpm for 4h, perform ultrasonic degassing for 30min to form the gel coating precursor.
[0068] Step S200: The gel coating precursor is coated onto the pretreated zinc substrate surface and dried in a vacuum environment to obtain the aqueous zinc-ion battery anode modification material. The zinc foil is first soaked in anhydrous ethanol and ultrasonically treated for 30 minutes to remove surface impurities, then placed in a vacuum drying oven for 30 minutes and dried. The gel coating precursor is then uniformly coated onto the zinc foil, and the foil is dried in a vacuum drying oven at 60°C for 10 minutes to obtain the gel-coated aqueous zinc-ion battery anode material, labeled as SLS+SA (unaged) anode modification material.
[0069] Assembly of aqueous zinc-ion batteries.
[0070] The aqueous zinc-ion battery anode material prepared by the above method was used as the positive and negative electrode materials, the separator was a glass fiber separator, and the electrolyte was 2.0 M ZnSO4. A symmetrical battery was assembled.
[0071] The following section combines the characterization results of the materials obtained from each embodiment and comparative example, as well as the performance test results of batteries assembled using these materials (i.e., Figures 1 to 6 (As shown), the advantages of the present invention will be further explained.
[0072] Figure 1 , Figure 2 The SEM image of the prepared material shows its size and morphology. Figure 3 The figure shows the electrochemical impedance spectroscopy (EIS) curve of the battery. Impedance is a vector, with the horizontal axis Z' being its real part and the vertical axis (Z") being its imaginary part. Figures 4 to 6 This is a cyclic curve graph, with the horizontal axis representing time and the vertical axis representing voltage. Test conditions: current density 0.5 mA cm⁻¹. -2 Surface capacity is 0.5mAh cm -2 .
[0073] Regarding Comparative Example 1 (using the "SA+SLS" order): The prepared anode material exhibited obvious localized agglomeration on its surface under a scanning electron microscope (SEM), indicating poor coating uniformity. When this anode was assembled into a symmetrical cell, its interfacial impedance was 408 Ω at 0.5 mA cm⁻¹. -2 A short circuit occurred after about 900 hours of cycling at a current density, and the voltage polarization curve fluctuated significantly, showing poor cycling stability and a relatively obvious dendritic short circuit phenomenon.
[0074] Regarding Example 1 (using the "SLS+SA" sequence): The prepared anode material exhibits a uniform and smooth surface morphology, with no obvious agglomeration observed. The interfacial impedance of the corresponding symmetrical cell is significantly reduced to 185 Ω at the same current density (0.5 mA cm⁻¹). -2 It exhibits a cycle life exceeding 2000 h and a stable voltage polarization curve, demonstrating excellent interface stability and cycle performance.
[0075] Regarding Example 2 (using the "SLS+CMC" sequence) The resulting negative electrode material also exhibits a relatively uniform surface morphology, and its symmetrical cell interfacial impedance is 174 Ω at 0.5 mA cm⁻¹. -2 Under these conditions, the cycle life is approximately 1800 h, and the voltage polarization curve is relatively stable, indicating that this type of sequence can also improve the interface structure and electrochemical performance to some extent.
[0076] The order of addition directly affects the cycle stability of the electrode. Based on the comparison results of Comparative Example 1, Example 1, and Example 2, it is evident that the addition order of "first adding the functional component containing sulfonic acid groups, then adding the polysaccharide anionic polymer material" (e.g., SLS+SA) effectively suppresses local aggregation of polysaccharide molecular chains, allowing the polysaccharide anionic polymer material to achieve more uniform dispersion in the functional component system containing sulfonic acid groups. This significantly reduces interfacial impedance and improves the cycle stability of the battery. Conversely, when the reverse order is used (e.g., SA+SLS), a high-viscosity polysaccharide system is formed first, making it difficult for the subsequently added functional component to disperse uniformly, resulting in an uneven coating structure and a significant deterioration in electrochemical performance.
[0077] Regarding Example 3 (using the "SBMA+SA" sequence) and Example 4 (using the "SBMA+CMC" sequence): The negative electrode materials obtained in Examples 3 (SBMA+SA) and 4 (SBMA+CMC) have uniform surface morphology, and their symmetrical cell interface impedances are approximately 208 Ω and 224 Ω, respectively, at 0.5 mA cm⁻¹. -2 The cycle life exceeded 1600 h, further verifying the universality of the feeding sequence of "adding functional components first and then polysaccharides" in different material combinations.
[0078] Regarding Comparative Example 2 (using the "SA+SBMA" order), Comparative Example 3 (using the "CMC+SLS" order), and Comparative Example 4 (using... (Use "CMC+SBMA" in order) Comparative Examples 2, 3, and 4 investigated different reverse feeding sequences. The results showed that the anode materials obtained by the above reverse sequences all exhibited varying degrees of local agglomeration under SEM, with a significant increase in interfacial impedance (approximately 356~477Ω) and a substantial reduction in cycle life, further confirming the decisive role of the feeding sequence in coating uniformity.
[0079] Regarding Comparative Examples 5 and 6 The pure polysaccharide-coated anodes obtained in Comparative Examples 5 (SA only) and 6 (CMC only), despite having relatively smooth surface morphology, exhibited high interfacial impedance in symmetrical cells and cycle lives of less than 400 h, with polarization voltage gradually increasing with cycling. This indicates that, in the absence of functional components, pure polysaccharide coatings cannot effectively suppress side reactions and construct efficient ion conduction channels, further confirming the necessity of introducing sulfonic acid group components.
[0080] Regarding Comparative Example 7 Comparative Example 7 used the same correct feeding sequence as Example 1 (SLS first, then SA), but omitted the static aging step. The resulting negative electrode material was at 0.5 mA cm⁻¹. -2The cycle life was significantly shortened (approximately 1200 h), and the voltage polarization curve showed increased fluctuations. This indicates that relying solely on the correct feeding sequence without static aging is insufficient to achieve a thermodynamically stable equilibrium configuration for the active functional groups, resulting in inadequate uniformity of the ion conduction channels and an inability to fully leverage the coating's regulatory effect on zinc deposition / dissolution behavior. This demonstrates that a specific feeding sequence combined with the static aging process synergistically constitutes the core process characteristics for achieving molecular-level uniform dispersion and long-term cycle stability.
[0081] Based on the above comparison, this invention achieves molecular-level uniform dispersion between functional components and polysaccharide macromolecules through the synergistic combination of a specific feeding sequence and a static aging process, significantly improving the interfacial stability and long-term cycling performance of the gel-coated modified zinc anode.
[0082] This invention reveals that the order of addition has a decisive influence on the microstructure of the precursor fluid. If high-molecular-weight polysaccharides are added first, the solution viscosity will increase rapidly, resulting in steric hindrance and encapsulation, preventing subsequently added functional components (such as SLS) from entering the inter-chain spaces and causing only macroscopic accumulation. Experiments have shown that not following the specific addition order described in this invention (see Comparative Example 1) will lead to a significant increase in the interfacial impedance of the coating and a substantial reduction in cycle life.
[0083] The hydrogel matrix material used in this invention is a polysaccharide anionic polyelectrolyte rich in free carboxyl groups. This type of material is characterized by its molecular chains being rich in carboxyl groups (…). COO - It possesses excellent hydrophilicity and the ability to form thermally irreversible gels through ionic bonds (such as with divalent zinc ions).
[0084] In embodiments of the present invention, the polysaccharide anionic polyelectrochemical material includes at least one of sodium alginate (SA) and sodium carboxymethyl cellulose (CMC), which can be used alone or in combination, or can be blended and modified with other natural or synthetic polymers.
[0085] In this embodiment of the invention, to avoid the self-aggregation of these polysaccharide macromolecules during solution concentration and film formation due to intermolecular hydrogen bonding, which would lead to local enrichment of functional groups and a decrease in coating uniformity, the above-mentioned preparation embodiment of the invention introduces a functional component rich in sulfonic acid groups. This functional component includes at least one of sodium lignin sulfonate (SLS) and sulfobetaine methacrylate (SBMA). The sulfonic acid groups of the functional component ( SO3 -It possesses stronger ionization ability and negative charge density, which can construct an effective electrostatic shielding environment between polysaccharide macromolecular chains, inhibiting their aggregation. At the same time, by dissolving the functional components in water first through a specific feeding sequence, and then adding the polysaccharide material, the functional components can achieve uniform dispersion and full interpenetration of the molecular level in the polysaccharide matrix.
[0086] This invention, through a specific static aging process, induces active functional groups to reach a thermodynamically stable equilibrium configuration, thereby forming highly uniform ion conduction channels during in-situ gelation. This is one of the core features of this invention that enhances cycle stability. Compared with other aqueous zinc-ion battery anode modification materials, this invention uses a simple blade coating method to prepare a gel coating for aqueous zinc-ion battery anode modification.
[0087] Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.
Claims
1. A gel-coated modified aqueous zinc-ion battery anode material, characterized in that, include: Zinc matrix; as well as, A gel coating formed on the zinc substrate.
2. The negative electrode material according to claim 1, characterized in that, The gel coating is formed by uniformly dispersing polysaccharide anionic polyelectrolyte in a solution of functional material and then sequentially allowing it to stand at room temperature for aging and ultrasonic degassing. The functional material contains sulfonic acid groups, and the polysaccharide anionic polyelectrolyte contains free carboxyl groups.
3. The negative electrode material according to claim 2, characterized in that, The polysaccharide-based anionic polyelectrolyte includes sodium alginate (SA), sodium carboxymethyl cellulose (CMC); and / or, The functional materials include sodium lignosulfonate (SLS) and sulfobetaine methacrylate (SBMA).
4. A method for preparing a gel-coated modified aqueous zinc-ion battery anode material, characterized in that, The preparation method includes: Step S100: Add functional materials to deionized water to form a solution, and uniformly disperse polysaccharide anionic polyelectric materials in the solution. After stirring, allow the mixture to stand at room temperature for aging and then degas it by ultrasonication to form a gel coating precursor. The functional materials contain sulfonic acid groups, and the polysaccharide anionic polyelectric materials contain free carboxyl groups. Step S200: Coat the gel coating precursor onto the surface of the pretreated zinc substrate and dry it in a vacuum environment to obtain the gel coating modified aqueous zinc-ion battery anode material.
5. The preparation method according to claim 4, characterized in that, The polysaccharide-based anionic polyelectrolyte includes sodium alginate (SA), sodium carboxymethyl cellulose (CMC); and / or, The functional materials include sodium lignosulfonate (SLS) and sulfobetaine methacrylate (SBMA).
6. The preparation method according to claim 4, characterized in that, The time for aging at room temperature is 2-10 hours, and the temperature is 20-30℃.
7. The preparation method according to claim 4, characterized in that, The amount of polysaccharide anionic polyelectrolyte rich in free carboxyl groups is 0.2~1g, the amount of functional component rich in sulfonic acid groups is 0.01~0.1g, and the amount of deionized water is 10~20mL.
8. The preparation method according to claim 4, characterized in that, The thickness of the gel coating precursor coated on the zinc substrate surface is 100~250μm.
9. An aqueous zinc-ion battery, characterized in that, This includes electrode sheets prepared from aqueous zinc-ion battery anode materials according to any one of claims 1 to 3 or prepared by any one of claims 4 to 8.
10. The aqueous zinc-ion battery according to claim 9, characterized in that, The aqueous zinc-ion battery includes coin cells and full cells.
